Quantificação do fármaco amoxicilina nos recursos hídricos do município de Inconfidentes-MG - Silva, Bruna Melo Da (2024)
Currently, water quality is threatened by the presence of emerging contaminants. Among these, pharmaceuticals deserve special attention, whether intended for human or veterinary consumption, especially considering that over the years, medications have been formulated with more potent active ingredients, which indicates great concern regarding their disposal. These contaminants reach water resources mostly through sewage treatment systems, which are not fully effective in containing this waste within the legal limits, which, together with the clandestine discharge of sewage into water and the incorrect disposal of expired and unused medications, in addition to medications used in animals, which, despite their low concentrations, still indicate toxicity to some fish, mollusks and humans. Therefore, studies aimed at quantifying these contaminants in water resources are necessary. To this end, priority was given to detecting the drug amoxicillin, one of the most consumed antibiotics in the municipality of Inconfidentes-MG. The sampling consisted of 7 collection points, 3 replicates along the Pitanga River, 3 replicates along the Mogi Guaçu River and the last one coming from the treated water of Copasa. HPLC and UV-Vis were used for the detection and quantification of the drug. The methodology was subjected to the validation parameters: precision, accuracy and linearity and the results to a completely randomized design, in addition to the Shapiro-Wilk test. In turn, the samples were characterized according to the parameters of pH, dissolved oxygen, temperature, conductivity, oxidation/reduction potential and salinity. The results indicated that although there was no significant difference between the three treatments, the presence of the drug amoxicillin was observed in all points studied. Therefore, the average concentration in the treatments ranged from 21.1 to 34 µg/L. However, in the present study the variables studied demonstrated a low correlation with the concentration. Thus, it is concluded that a reassessment of the municipality's basic sanitation is necessary, since the concentration found was higher than that permitted according to the Environmental Protection and Heritage Council of Australia, which is 0.0015 mg/ml, together with the adoption of educational measures for the population as a whole regarding the disposal and indiscriminate use of medicines in general, especially antibiotics.